2017
DOI: 10.3389/fpls.2017.00536
|View full text |Cite
|
Sign up to set email alerts
|

SNP Discovery and Genetic Variation of Candidate Genes Relevant to Heat Tolerance and Agronomic Traits in Natural Populations of Sand Rice (Agriophyllum squarrosum)

Abstract: The extreme stress tolerance and high nutritional value of sand rice (Agriophyllum squarrosum) make it attractive for use as an alternative crop in response to concerns about ongoing climate change and future food security. However, a lack of genetic information hinders understanding of the mechanisms underpinning the morphological and physiological adaptations of sand rice. In the present study, we sequenced and analyzed the transcriptomes of two individuals representing semi-arid [Naiman (NM)] and arid [Shap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 57 publications
1
9
1
1
Order By: Relevance
“…This level of divergence was higher than those usually observed among alleles of single genetic loci in plants (e.g. Brown et al , 2004; Tatarinova et al , 2016; Zhao et al , 2017). Phylogenetic analyses of the last intron of AdPCS1-3 isolated from four different Arundo species clearly showed that divergence among sequences predated the evolutionary split among species and ruled out recombination (Supplementary Fig.…”
Section: Resultscontrasting
confidence: 61%
“…This level of divergence was higher than those usually observed among alleles of single genetic loci in plants (e.g. Brown et al , 2004; Tatarinova et al , 2016; Zhao et al , 2017). Phylogenetic analyses of the last intron of AdPCS1-3 isolated from four different Arundo species clearly showed that divergence among sequences predated the evolutionary split among species and ruled out recombination (Supplementary Fig.…”
Section: Resultscontrasting
confidence: 61%
“…It is widely distributed in mobile sand and semi-fixed dunes across all the arid and semi-arid regions in Central Asia, the Caucasus, Mongolia, and Siberia, including the Qinghai-Tibet Plateau ( Wu et al, 2003 ). It can survive in extremely high temperatures and drought conditions and can tolerate sand burial ( Chen et al, 2014 ; Li et al, 2015 ; Zhao et al, 2017 ). Since the withered plants can reduce wind velocity by more than 90%, they also acted as nutrient providers and reservoirs with a rich source of carbon and nitrogen in infertile soil environments.…”
Section: Introductionmentioning
confidence: 99%
“…Physiology and morphology of sand rice are ideally adapted to the extreme desert conditions [ 13 ], which make A. squarrosum interesting for studying its genomic basis of xeric adaptations. In the last 10 years, there were several works dedicated to the search of candidate genes responsible for the tolerance to heat and drought stresses [ 14 ]. One of the current primary goals is the domestication of sand rice in desert environments [ 15 ] via development of plants with larger grains and higher yield, and to exclude unfavorable phenotypic traits such as seed shattering, thorns, etc.…”
Section: Introductionmentioning
confidence: 99%